APPLICATION OF ELICITOR FOR PRODUCTION OF SAPONINS FROM IN VITRO PANAX CULTURES - Nhat Linh, Nguyen Thi; Loc, Nguyen Hoang; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2018)
The Panax ginseng species are traditional medicinal herbs having high value. The major pharmacologically active components are the ginsenosides of saponin group, which are dammarane type triterpene glycosides containing a tetracyclic glycose. Ginseng saponin, one of the secondary metabolites, is necessary for the growth and development of Panax genus plants. In pharmaceutical industry, triterpene saponins were purified to produce drugs for its promising healing and restorative properties. However, commercial applications are still obstacle for practical problems, because ginseng natural resources are rarely precious; and ginseng resources from field have low and variable yields dependent on season or quality of soil. Moreover, triterpene saponins have complex structures, making chemical synthesis an economically uncompetitive option for large-scale production. A current alternative optimal solution that is popular in the world is the application of cell and tissue culture to produce a large of cell or root yield in short time. But the difficulty in producing triterpene saponins from in vitro culture is that the triterpene saponin content is much lower than natural. To increase the triterpene saponin content, elicitors are added to the culture medium. Based on the effect of the elicitor, metabolic engineering in vitro is also able to enhance the overexpression of genes which translated enzymes or signals producing saponin in the isoprenoid pathway. Application of elicitor researches could improve triterpene saponin yields or adjust specific desired triterpene saponins from in vitro ginseng culture. Therefore, we review the recent studies of elicitor in Panax genus cultures and saponin biosynthetic gene to study and assess the efficiency of elicitors in triterpene saponin production and metabolic engineering of triterpene saponins.